Reduction of Salmonella Typhimurium by Fermentation Metabolites of Diamond V Original XPC in an In Vitro Anaerobic Mixed Chicken Cecal Culture - Rubinelli, Peter; Roto, Stephanie; Kim, Sun Ae; Park, Si Hong; Pavlidis, Hilary O.; McIntyre, Don; Ricke, Steven C. (Frontiers in Veterinary Science, 2016)
Fermentation metabolites of Diamond V Original XPCTM (XPC), a biological product derived from yeast fermentation, were evaluated for their ability to reduce the Salmonella Typhimurium population using an in vitro mixed anaerobic culture system containing cecal microbiota to simulate chicken hindgut conditions. Four different samples were prepared: anaerobic mixed culture containing 1) feed only, 2) cecal only (ceca were harvested from 42 days old broiler chickens), 3) feed and cecal contents, and 4) feed, cecal contents, and 1% XPC. Two experimental conditions were investigated: Group 1, in which the cecal content was added at the same time as a S. Typhimurium marker strain and Group 2, in which the cecal content was pre-incubated for 24 h prior to the inoculation with the S. Typhimurium marker strain. The mixed cultures were incubated anaerobically at 37°C and the S. Typhimurium marker strain was enumerated at 0, 24, and 48 h. Analysis of short chain fatty acids was also conducted for 24 h. In the Group 1 experiment, adding XPC did not exhibit significant reduction of S. Typhimurium. However, the presence of XPC resulted in rapid reduction of S. Typhimurium in Group 2. S. Typhimurium was reduced from 6.81 log10 CFU/ml (0 h) to 3.73 log10 CFU/ml and 1.19 log10 CFU/ml after 24 and 48 h, respectively. These levels were also 2.47 log10 and 2.72 log10 lower than the S. Typhimurium level recovered from the control culture with feed and cecal contents but without XPC. Based on these results, it appears that the ability of XPC to reduce S. Typhimurium requires the presence of the cecal microbiota. Short chain fatty acid analysis indicated acetate and butyrate concentrations of cultures containing XPC were 2 fold greater than the control cultures by 24 h of anaerobic growth. Results from the present study suggest that dietary inclusion of XPC may influence cecal microbiota fermentation, and has the potential to reduce Salmonella in the cecum. Implications of these findings suggest XPC may decrease pre-harvest levels of Salmonella in broilers and layers.